Sharia Pawnshops As An Alternative To Meeting Social Needs Sociological Review - Ulya Adila, Hafidah; Arifin, Tajul; Abdal, Abdal (Zona Law And Public Administration Indonesia, 2024)
This research aims to find out how Sharia Pawnshops can be an alternative to meeting social needs, a sociological review. This research uses an empirical approach with descriptive qualitative methods. With the type of research study literature (Library Research). The result of this research is that Pegadaian is a form of non-bank financial institution intended for the wider community with middle to lower income who need funds immediately. These funds are used to finance certain needs. The use of Pegadaian Syariah as an alternative to meeting the needs of the community has a broad impact on various aspects of economic and social life. It assists the community in the fulfillment of their financial needs while adhering to Islamic sharia financial principles. The use of Islamic Pawnshops as an alternative to meeting the needs of the community has a number of significant impacts, including: the use of Islamic pawnshops helps individuals and families in the fulfillment of their financial needs. For SMEs that can use loans and financing, it creates jobs, and contributes to local economic growth. The use of Pegadaian Syariah can have social impacts such as reducing poverty levels, reducing economic inequality, and supporting social stability within communities